Bird Diversity and Structure in Different Land-use Types in Lowland South Central Mindanao, Philippines - Krizler Cejuela Tanalgo; John Arislyn Fuentes Pineda; Maricel Estolloso Agravante; Zabide Mamalo Amerol (Tropical Life Sciences Research, 2015)
Birds are crucial to maintaining the balance of many ecosystems by providing various ecological services. The diversity of birds and their feeding guilds in different land-use types were investigated in south-central Mindanao to elucidate the effect of disturbance and habitat modification on bird communities. Point count method was employed to identify birds in three habitat types: i) agroforests; ii) ricefields; iii) roads and heavily disturbed areas. A total of 1114 bird sightings were recorded that included 33 species of 24 families; of these, 3 were Philippine endemics, and 5 were migrant species. Among all of the habitat types, the highest species diversity was found in agroforests (1/D = 16.148), and the lowest was recorded from roads and heavily disturbed habitats. The species composition of agroforests was more similar to ricefields than to areas with high levels of disturbance, such as roads. The characteristic of the vegetation and the availability of food resources may be vital to the diversity of birds in every habitat as evidenced by the high species richness of frugivores and insectivores in agroforests and ricefields, respectively, where food source is largely available. The observation of Streptopelia tranquebarica was a new record for Mindanao, and it was particularly sighted in ricefields. Therefore, this study indicates that land-use change and modification may alter bird diversity structure, and the maintenance of the vegetation in land-use types as food and resource, and as habitat is essential to the conservation of the native and ecologically-important bird species in south-central Mindanao. Burung-burung penting untuk mengekalkan keseimbangan ekosistem dengan membekalkan pelbagai servis ekologi. Kepelbagaian burung-burung and perseikatan pemakanan dalam pelbagai jenis guna-tanah telah dikaji di selatan-tengah Mindanao untuk menjelaskan kesan-kesan gangguan dan pengubahsuaian habitat komuniti burung. Kaedah bilang titik telah digunakan untuk mengenal pasti burung-burung dalam tiga jenis habitat: i) hutan agro; ii) sawah padi; iii) jalan raya dan kawasan yang mengalami gangguan yang teruk. Sebanyak 1114 burung telah dilihat dan direkodkan, termasuk 33 spesies daripada 24 famili; daripada ini, 3 merupakan spesies endemik Filipina, dan 5 merupakan spesies pehijrah. Daripada semua jenis habitat, diversiti spesies yang tertinggi telah dijumpai di hutan agro (1/D = 16.148), dan yang terendah direkodkan daripada jalan raya dan kawasan yang mengalami gangguan yang teruk. Komposisi spesies hutan agro lebih mirip dengan sawah padi berbanding dengan kawasan yang mengalami gangguan yang teruk, seperti jalan raya. Sifat-sifat tumbuhan dan ketersediaan sumber makanan mungkin penting untuk kepelbagaian spesies di setiap habitat seperti yang terbukti oleh kekayaan spesies frugivor dan insektivor yang tinggi di hutan agro dan sawah padi, masing-masing, yang mempunyai sumber makanan yang banyak. Pencerapan terhadap Streptopelia tranquebarica merupakan rekod baru untuk Mindanao, dan secara spesifiknya ia ditemui di sawah padi. Maka, kajian ini menunjukkan bahawa perubahan guna-tanah mungkin boleh mengubahsuai struktur kepelbagaian burung, dan pengekalan tumbuhan dalam jenis guna-tanah sebagai makanan dan sumber, dan sebagai habitat penting untuk pemuliharaan spesies-spesies burung natif dan penting secara ekologi di selatan-tengah Mindanao.